2018
DOI: 10.1038/s41408-018-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlation between multiple myeloma and chronic lymphocytic leukaemia provides evidence for shared aetiology

Abstract: The clustering of different types of B-cell malignancies in families raises the possibility of shared aetiology. To examine this, we performed cross-trait linkage disequilibrium (LD)-score regression of multiple myeloma (MM) and chronic lymphocytic leukaemia (CLL) genome-wide association study (GWAS) data sets, totalling 11,734 cases and 29,468 controls. A significant genetic correlation between these two B-cell malignancies was shown (Rg = 0.4, P = 0.0046). Furthermore, four of the 45 known CLL risk loci were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…36,43,44,89,90 Albeit preliminary, evidence for a shared susceptibility between different hematological malignancies consistent with our observations has been proposed from recent analyses of GWAS data. 91,92 A component of the FRR may also be explained by shared environmental risk factors, although the magnitude of their role in explaining familial aggregation has been debated. [93][94][95][96] To date, few robustly identified environmental risk factors for hematological malignancy have been described, with examples including infection with EBV, HIV, HTLV, and Helicobacter pylori, as wel as benzene, cytotoxic therapy, and ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…36,43,44,89,90 Albeit preliminary, evidence for a shared susceptibility between different hematological malignancies consistent with our observations has been proposed from recent analyses of GWAS data. 91,92 A component of the FRR may also be explained by shared environmental risk factors, although the magnitude of their role in explaining familial aggregation has been debated. [93][94][95][96] To date, few robustly identified environmental risk factors for hematological malignancy have been described, with examples including infection with EBV, HIV, HTLV, and Helicobacter pylori, as wel as benzene, cytotoxic therapy, and ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…MPNs are categorized by the WHO into numerous subclasses, and this is used for sporadic illness more willingly than familial cases, one of which is PV [ 9 ]. PV 2016 WHO criteria for diagnosis consist of one minor criterion and three main criteria [ 4 ]. The main criteria are: hematocrit >49% (men)/>48% (women), or hemoglobin >16.5 g/dL and >16.0 g/dL in men and women, respectively, or rise in red cell mass; bone marrow biopsy exhibiting hypercellularity for age with trilineage growth (panmyelosis) containing prominent granulocytic, erythroid, and megakaryocytic proliferation with different size pleomorphic, and mature megakaryocytes; and the existence of JAK2 or JAK2 exon 12 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…His JAK2 V617F mutation screen came back positive for exon 14. He had a low erythropoietin level of 1.2 (reference range: 3.7 to 36 IU/L) and had bone marrow and peripheral blood findings in accordance with MPN for which he met the 2016 WHO criteria for PV [ 4 ]. He was treated with hydroxyurea 500 mg twice per day and repeated phlebotomies, when needed, to keep his hematocrit level lower than 45%.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently genomic studies have identified common susceptibility loci between chronic lymphocytic leukemia (CLL), hodgkin lymphoma (HL), and multiple myeloma demonstrating shared genetic etiology between these B-cell malignancies (BCM) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%